SUBALTERN DAN KEBIJAKAN PEMBANGUNAN REKLAMASI PANTAI DI KOTA MAKASSAR - Ruslin, Ismah Tita (Jurnal Politik Profetik, 2017)
This article reflects the role of fishermen as subaltern group in the politic of sea side reclamation development in Makassar city. Subaltern may be defined as suppressed, inferior and powerless subject in representing the subjects themselves. The dynamic of development in urban areas is strictly attached to the management of the leading regime which produces urban political planning. The development vision of Makassar city to combine the concept of world city and local wisdom is more less a series of sustainable development of old city developed in the perspective of developmental colonialism and recently restructured in that of economic imperialism. When development is correlated with surplus achievement, the result may be twofold. In one hand, it will create new wealthy parties, while at the same time, communal poverty and misery is frequently an immediate consequence of the development itself. Indeed, development is not merely provided by nature. It is an unavoidable consequence of political process and negotiation by political actors, which may involve intrigues, fight for interest, and chase of power with political implications.